Learning Transformation: The Role of Interactive Media in the Implementation of the Independent Curriculum in Elementary Schools - Suryadi, Ahmad; Arisetyawan, Andika (International Conference on Elementary Education, 2025)
The Merdeka Curriculum (Independent Curriculum) demands a learning transformation toward a more flexible, student-centered approach, where interactive media is expected to play a key role. However, a comprehensive synthesis of how this media is being implemented, its consistent impact, and the real-world challenges in Indonesian Elementary Schools remains lacking. This study aims to analyze the role of interactive learning media in supporting the implementation of the Merdeka Curriculum in Elementary Schools. This study uses a Systematic Literature Review (SLR) methodology adhering to the PRISMA protocol. An article search (2020–2024) was conducted using Publish or Perish on the Google Scholar, Scopus, and SINTA databases. From 985 identified articles, 10 articles were selected through a rigorous screening and criteria process for qualitative synthesis. The synthesis results show a strong consensus: (1) Interactive media consistently improves both cognitive (learning outcomes) and affective (motivation, learning interest, critical thinking) domains, aligning with global trends. (2) Two dominant media categories were identified: Low-Code/No-Code platforms (like Canva and LearningApps) and Developed Applications (such as Android-based media). (3) A